Effect of biofertilizers on growth of aloe (Aloe barbadensis Miller) and gel quality under different soil moisture contents - Juan Antonio Núñez Colima (REVISTA CHAPINGO SERIE HORTICULTURA, 2018)
Aloe (Aloe barbadensis Miller) is a water deficit-tolerant plant. Products obtained from the leaf have a high commercial value in the medical, food and cosmetological industries. The aim of this study was to evaluate the growth and development of aloe (Aloe barbadensis M.) plants and the quality of its gel when applying bat guano extract (BGE) and seaweed extract (SE) in different soil moisture contents. A split-plot randomized block design was used with three replicates. The large plots were soil moisture contents: low (13 to 17 %), medium (18 to 22 %) and high (23 to 27 %); the medium plots were the BGE doses (0 and 20 L∙ha-1∙year-1), and the small plots the SE doses (0 and 20 L∙ha-1∙year-1). At 152, 238 and 458 days after the first application of the biofertilizers (DAFAB), plant height (cm), leaf length, width and thickness (cm), gel weight (g) and concentration of total soluble solids (TSS, %) in the gel were measured. Leaf width and thickness were higher when the soil moisture content was close to field capacity (23 to 27 %), while leaf length and width were higher in the first two evaluations when the moisture content was medium (18-22 %). The TSS concentration did not show significant statistical differences (P ≤ 0.05) in any treatment. At the end of the evaluation cycle (458 DAFAB), BGE increased leaf width and thickness.